Fracture and contralateral dislocation of the twin facet joints of the lower cervical spine - Ngo, Ly Minh (Springer-Verlag, 2011)
PURPOSE: The combination of a facet fracture and a contralateral facet dislocation at the same intervertebral level of the cervical spine (a fracture and contralateral dislocation of the twin facet joints) has not been described in detail. The aims of this study are to report a series of 11 patients with this injury, to clarify the clinical features and to discuss its pathomechanism. METHODS: Among 251 patients with lower cervical spine fractures and/or dislocations surgically treated, 11 (9 males and 2 females, averaged age, 52 years) had this kind of injury. Medical charts and medical images were reviewed retrospectively. RESULTS: Injury levels were C4-5, C5-6 and C6-7 in 1, 4 and 6 patients, respectively. A fracture was found at the superior facet in 6, and at the inferior facet in 5. The anterior displacement of the vertebral body ranged from 7 to 19 mm. The unilateral horizontal facet appearance on an anteroposterior radiograph and the triple image on a CT composed of a separated fracture fragment, the base of the fractured facet, and the neighboring non-fractured facet were characteristic. All patients had neurological deficits from Frankel A to D, and were surgically treated by posterior fusion using wire or cable, or combined anterior and posterior spinal fusion. CONCLUSIONS: The fracture and contralateral dislocation of the twin facet joints can cause severe neurological deficits because of its gross anterior displacement. Its plausible pathomechanism is extension force exerted to the cervical spine when it is maximally bent laterally.